Bio-cooling façade in tropical climate - Nurul Sonda Fadhila; Miktha Farid Alkadri; Ova Candra Dewi (Center for Science and Technology, IAIN Surakarta, 2024)
The purpose of this paper is to explore how building design requires consideration of both energy consumption and environmental impacts of the construction and maintenance processes. The increasing energy consumption and construction waste are concerning trends within the building industry. In response to this issues, the concept of circular economy has gained prominence, emphasizing the need to restore, rebuild, and regenerate resources in a sustainable manner. This research focused on Bio-Cooling Façades (BCF) in tropical climates through the assessment of four parameters including the biomaterial, cooling façade, energy consumption, and building circularity. This was conducted through a comparative analysis of existing and eight proposed BCF configurations designed to reduce energy consumption and increase building circularity. The results show that applying BCF at a glazing size of 40% reduces solar heat radiation, lowers building energy consumption, and minimizes potential construction material waste in countries with tropical climates. These findings assist architects and the industry in defining the optimal building façades for cooling, ultimately reducing energy consumption.